Industrial safety at chinese enterprises on the example of zijin mining company - Tverdokhliebova, N. Ye.; Liu Yujun (Національний технічний університет "Харківський політехнічний інститут", 2024)
China's scientific and technological strength is moving from quantitative accumulation to qualitative leap, from point breakthrough to system capacity improvement, and making new historic achievements in scientific and technological innovation.
Keywords: safety production license; production safety; control occupational hazards